Adverse Childhood Experiences in the Lives of Female Sex Offenders. (June 2015) - Levenson, Jill S.; Willis, Gwenda M.; Prescott, David S.
This study explored the prevalence of early trauma in a sample of U.S. female sexual offenders ( N = 47) using the Adverse Childhood Experiences (ACE) scale. Compared with females in the general population, sex offenders had more than three times the odds of child sexual abuse, four times the odds of verbal abuse, and more than three times the odds of emotional neglect and having an incarcerated family member. Half of the female sex offenders had been sexually abused as a child. Only 20% endorsed zero adverse childhood experiences (compared with 35% of the general female population) and 41% endorsed four or more (compared with 15% of the general female population). Higher ACE scores were associated with having younger victims. Multiple maltreatments often co-occurred in households with other types of dysfunction, suggesting that many female sex offenders were raised within a disordered social environment by adults with problems of their own who were ill-equipped to protect their daughters from harm. By enhancing our understanding of the frequency and correlates of early adverse experiences, we can better devise trauma-informed interventions that respond to the clinical needs of female sex offender clients.